Future Shock: Editing for" Ad-hocracy" - Donald K. Childers (Journal of Applied Communications, 1974)
Future structure of organizations in government, education, and business will be characterized - if not already - by many task forces, project teams, interdisciplinary groups, multidisciplinary teams, multifunctional projects, and other impressively named, committee-like groups.